DICTATORSHIP, MACHISMO, AND THE CUBAN EXILE DRAMA IN A TRAGICOMIC MODE: CRISTINA GARCÍA’S “KING OF CUBA” - POPESCU, Veronica Tatiana (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Dictatorship, Machismo, and the Cuban Exile Drama in a Tragicomic Mode: Cristina García’s King of Cuba. Three years before the death of Fidel Castro, Cuban American author Cristina García published a fictional account of the Cuban dictator’s death in a darkly funny and sentimental story of intertwined destinies, ironies of fate, machismo, failure and suffering. With El Comandante and a fellow octogenarian émigré as protagonists, García launches into a fictional exploration of Cuban masculinity, machismo, the dictator’s fate, vanity, and failure. Written in what I will argue is a tragicomic mode, balancing the tragic and the comic, the horrendous and the laughable, the pitiful and the ridiculous, the novel reflects different perspectives on sensitive topics for Cubans on both sides of the Florida Straits, challenging preconceived ideas and inviting the reader to reflect on the relativity of truth. REZUMAT. Dictatură, machism și drama comunității cubaneze din Statele Unite în manieră tragi-comică: King of Cuba de Cristina García. Cu trei ani înaintea morții lui Fidel Castro, autoarea americană de origine cubaneză, Cristina García, publica o întruchipare imaginară a morții dictatorului cubanez într-o poveste sentimentală, scrisă cu umor negru, în care găsim destine încrucișate, ironii ale sorții, machism, ratare și suferință. Protagoniștii sunt doi octogenari: El Comandante și un cubanez care trăiește în exil. Cu ajutorul lor García abordează teme precum masculinitate cubaneză, machism, condiția dictatorului, vanitate și ratare. Scrisă într-o manieră tragi-comică, alternând în mod echilibrat tragicul și comicul, oribilul și rizibilul, jalnicul și ridicolul, romanul reflectă diferite perspective asupra unor teme sensibile pentru comunitățile cubaneze de o parte și de alta a Strâmtorii Florida, atacând ideile preconcepute și invitându-l pe cititor să reflecteze asupra relativității adevărului. Cuvinte-cheie: Fidel Castro, dictatură, machism, comunitate cubanezo-americană, satiră, manieră tragi-comică